From What Works To What Makes Sense: A Quranic Wisdom-Based Leadership Model For Madrasah - Suhardi Suhardi (Universitas Muhammadiyah Tangerang, 2026)
The digital disruption era demands madrasah leadership capable of aligning technological transformation with Islamic values as institutional identity. This study aims to: (1) analyze the limitations of the what works approach in madrasah contexts amid digital disruption, (2) explore the potential of Quranic wisdom for developing adaptive and contextual sense-making leadership, and (3) formulate the integrative HSA2S leadership model (Hikmah, Syura, Amanah, Adil, and Sabr). The research employs interpretive qualitative library research; data were drawn from Quranic verses, thematic exegesis, and indexed journal literature (2019–2025). Analysis comprised thematic content analysis, hermeneutics, and theoretical synthesis. Findings indicate that the what works approach tends toward universalism, neglects the spiritual-cultural context of madrasah, and often produces standardized solutions that misalign with field realities. Conversely, the what makes sense paradigm grounded in Quranic wisdom is more appropriate as a basis for adaptive leadership. The study develops the HSA2S model, integrating Quranic wisdom with sense-making leadership principles and operationalizing it through four dimensions: spiritual, intellectual, social, and digital. Theoretically, the model enriches Islamic educational leadership scholarship; practically, it provides madrasah principals with an operational framework for sustainable, inclusive, and Islamically characterized digital transformation. Keywords: madrasah leadership, what makes sense, Quranic wisdom, digital transformation, sense-making leadership